ADOLESCENT REPRODUCTIVE HEALTH AND IMPLICATIONS FOR GROUP COUNSELING - Firsa, Ahmad Zaky; Adiwinata, Anne Hafina; Ramdhani, Rina Nurhudi (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Adolescent reproductive health is a crucial aspect of development, as it is directly related to their readiness to face physical, psychological, and social changes. This study aims to describe the level of adolescent reproductive health knowledge and its implications for group guidance services. The research method used is quantitative with a descriptive approach, employing a cross-sectional survey technique involving 393 eighth-grade students from three junior high schools in Cikampek. The research instrument was a questionnaire developed based on the ASRH-KASeQ.The results showed that the majority of students 292 individuals, or approximately 74 percent of the total respondents had a moderate level of reproductive health knowledge. These findings serve as the basis for designing a group guidance service implementation plan, in accordance with the Operational Guidelines for the Implementation of Guidance and Counseling (POP BK), aimed at improving students’ reproductive health knowledge.